Formulation and Evaluation of Oral Dispersible Tablets: A Study on Ibuprofen and Superdisintegrants - Ghorpade V.S (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study investigates the formulation and evaluation of oral dispersible tablets (ODTs) containing Ibuprofen and various superdisintegrants. The research aims to optimize formulation parameters to enhance tablet disintegration and dissolution. Results demonstrate the significant impact of superdisintegrants on tablet properties, offering potential advancements in drug delivery technology. Oral dispersible tablets (ODTs) are gaining popularity due to their ease of administration and rapid disintegration in the oral cavity, making them particularly beneficial for patients who have difficulty swallowing conventional tablets. Ibuprofen, a widely used nonsteroidal anti-inflammatory drug (NSAID), serves as an ideal model drug for this study due to its therapeutic relevance and formulation challenges. Superdisintegrants play a crucial role in ODT formulation by facilitating rapid tablet disintegration and drug release. The study utilized Ibuprofen as the active pharmaceutical ingredient (API), along with various superdisintegrants such as crospovidone, croscarmellose sodium, and sodium starch glycolate. Different formulations were prepared using direct compression method, varying the concentration of superdisintegrants to optimize tablet properties. Tablets were evaluated for parameters including disintegration time, hardness, friability, and dissolution profile using standard pharmacopoeia methods. Experimental results revealed that formulations containing higher concentrations of superdisintegrants exhibited faster disintegration times and improved dissolution rates compared to control formulations without superdisintegrants. Crospovidone demonstrated the most significant enhancement in tablet disintegration and dissolution efficiency among the superdisintegrants tested. The optimized formulation of Ibuprofen ODTs showed promising results in terms of rapid drug release and enhanced patient compliance.